Carbapenem‐resistant Acinetobacter baumannii acquired before liver transplantation: Impact on recipient outcomes. Issue 5 (26th April 2016) - Freire, Maristela Pinheiro; Pierrotti, Ligia Câmera; Oshiro, Isabel Cristina Villela Soares; Bonazzi, Patrícia Rodrigues; Oliveira, Larissa Marques de; Machado, Anna Silva; Van Der Heijden, Inneke Marie; Rossi, Flavia; Costa, Silvia Figueiredo; D'Albuquerque, Luiz Augusto Carneiro; Abdala, Edson
Abstract : Infection with carbapenem‐resistant Acinetobacter baumannii (CRAB) after liver transplantation (LT) is associated with high mortality. This study aimed to identify risk factors for post‐LT CRAB infection, as well as to evaluate the impact of pre‐LT CRAB acquisition on the incidence of post‐LT CRAB infection. This was a prospective cohort study of all patients undergoing LT at our facility between October 2009 and October 2011. Surveillance cultures (SCs) were collected immediately before LT and weekly thereafter, until discharge. We analyzed 196 patients who were submitted to 222 LTs. CRAB was identified in 105 (53.6%); 24 (22.9%) of these patients were found to have acquired CRAB before LT, and 85 (81.0%) tested positive on SCs. Post‐LT CRAB infection occurred in 56 (28.6%), the most common site being the surgical wound. Multivariate analysis showed that the risk factors for developing CRAB infection were prolonged cold ischemia, post‐LT dialysis, LT due to fulminant hepatitis, and pre‐LT CRAB acquisition with pre‐LT CRAB acquisition showing a considerable trend toward significance ( P = 0.06). Among the recipients with CRAB infection, 60‐day mortality was 46.4%, significantly higher than among those without ( P < 0.001). Mortality risk factors were post‐LT infection with multidrug‐resistant bacteria, LT performed because of fulminant hepatitis, retransplantation, prolonged cold ischemia, longer LT surgical time, and pre‐LT CRAB acquisition, the last showing a trend toward significance ( P = 0.08). In conclusion, pre‐LT CRAB acquisition appears to increase the risk of post‐LT CRAB infection, which has a negative impact on recipient survival. Liver Transplantation 22 615‐626 2016 AASLD.